Template para elaboração de uma unidade didática na perspectiva dos estudos sociorretóricos de gênero - Silva, Rosa Lídia da (2018)
This dissertation is inserted in the Research Line: Text and speech in the oral and written modalities of the Program of Postgraduate Studies in Portuguese Language. It is the study of a model whose purpose is to guide the writing process of the didactic unit document, by teachers authors or experts in the disciplines. We use the nomenclature didactic unit as a series of teaching and learning activities assembled and organized for learning purposes (LIBÂNEO; FREITAS, [2009]). This model, named didactic unit template, is built with the components of a didactic unit, and may contain autoforming features, which facilitate the production of the final document, even by less experienced authors. Our main objective was to better understand the template, its composition and socio-rhetorical organization, to reflect if and in what way it affects the quality of the material it supports, contributing to the teaching and learning process. We use as theoretical foundation the socio-rhetorical studies of gender. The authors consulted were Swales (1990; 2004); Miller (1984, 2014); Bhatia (1993, 2001, 2012); Bazerman (2000); Bazerman and Miller (2011); Aguiar (2011); Biasi-Rodrigues and Bezerra (2012); Campos (2014); Crescitelli and Campos (2015) and Motta-Roth (1998; 2004). Being restricted the access to templates, for reasons of copyright, we began our study by textbooks, in view of being a type of text whose components are included in didactic units and for having their use recognized in the support of educational activities. We analysed ten books and, of these, we selected two to present the more detailed analysis. Having obtained a template of allowed use, named as Template COL, we were able to analyse it and reproduce it here. This model was created by the Commonwealth of Learning (COL), an international organization supporting education, especially in less developed countries. For a second example, we describe the items of a didactic unit template, based on our experience working with this type of model. In these models, we identify rhetorical moves and steps, according to Swales' (1990) CARS Model, to better understand the organization and interrelationship of its elements. In the course of research, we have a contact with a case study of a researcher active in the development of education in Namibia (FRÖHLICH, 2008), which shows the practical use of the template to support authors, even with less experience. The contact with the Template COL and the reality in which it is used has shown us that – in addition to helping in the quality of the final document, as we have seen previously because of our professional experience – the application of templates can be a valuable resource, including in less favored regions. Analysis by socio-rhetorical principles allowed us to see the text through more than one approach, considering its objectives, its functioning and the people affected by it. For us, it has been evident that the careful planning of the didactic unit and the construction of its final document in an organized way are important so that it fulfills its purpose with students and teachers. In this composition, the author can be aided by the template, which also requires planning and constitutes a tool to support the preparation of documents for educational purposes